Expression of Protamine-1 Gene and Association with Interleukin-12 gene in Infertile Men: A Case-Control Study in Iraqi Patients - Samawi, Farah T.; Al-Dujaily, Saad S.; AL-Saidi, Muhanad K.; Abdulfattah, Shaimaa Y.; Saeed, Zinah Zaki (Iraqi Journal of Science, 2023)
Approximately 15% of all couples all over the world suffer from difficulty conceiving their first child. The word "infertility" is used to describe this problem. When a couple had regular, unprotected sexual intercourse for a year or longer, it indicates that they have been unsuccessful in their efforts to conceive. The current investigation aims to find out if there is a relationship between PROTAMIN-1(PRM-1) and INTERLEUKINE-12 (IL-12) gene expressions and their effect on the development of infertility. The current investigation comprised 100 teratozoospermia patients and 100 healthy fertile controls who had their semen examined. Samples were given by Al-Nahrain University’s Biotechnology Research Center and the Kamal Al-Samarie IVF Hospital in Baghdad, Iraq. Determinations Reverse Transcription quantitative Polymerase Chain Reaction (RT-qPCR) was employed to test the expression of the PRM gene in semen and blood samples, as well as the IL-12 gene in blood samples. And the titer of IL-12 was evaluated in the seminal plasma employing the Enzyme Linked Immune Sorband Assay (ELISA) technique. The difference between the mean threshold cycle (ΔCt) of PRM-1 and IL-12 mRNA in the infertile patient group versus the healthy control group was also statistically significant. Evaluating the means of 2 ̄ΔΔCt revealed an important finding, a decrease in the expression of PRM-1 mRNA in the infertile group in comparison to the control group in the two types of samples. Conversely, there was an increase in the expression of IL-12 mRNA between the two study groups. In infertile Iraqi men, the expression of the PRM-1 gene was found to be down-regulated, whereas the expression of the IL-12 gene was found to be up-regulated. Our data revealed the diagnostic value of these genes and might be considered as predictive biomarkers in infertile people with idiopathic infertility.